ANALISIS KINERJA WINDOWS SERVER DAN LINUX SERVER TERHADAP RESPONS TIME SQUID PROXY - parulian sirait; R.Fanry Siahaan (Journal Of Informatic Pelita Nusantara, 2019)
Use of bandwidth for Internet access can be maximized by using a proxy server usage. One is the Squid proxy server. The use squid as the proxy server will need to consider the operating system on the server and not known his best performance on what operating system. The study was conducted to compare the Squid proxy server response time when compared to its use on Windows servers and Linux servers. The test is to undertake the implementation of squid proxy server on Windows servers and Linux servers. Then, from the client computer done accessing the Internet from each server using a web browser Mozilla Firefox and Internet Explorer. For simplicity, this study uses a client with 10 times the test site access from the server. From the results of tests performed, we concluded that the application of the squid proxy server on a Linux server timenya better response from the Windows server. This is evidenced from the results of experiments showing changes in response time of the greatest site access is done from a Linux server.